ANALISIS HARGA GABAH KERING PANEN DAN HARGA BERAS PREMIUM TERHADAP NILAI TUKAR PETANI DI JAWA BARAT PERIODE 2019-2021 - Yulianti, Nanda Devi; Gunawan, Syahrul Ahmad; Hizbandyah, Baiturrahmi Nur; Brata, Anggita Shakarine; Maesaroh, Syti Sarah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
A measure of farmer welfare knowledge is determined by the farmer exchange rate (NTP). Factors that affect farmers’ wealth are the price of harvested grain (GKP) and the price of premium rice. The purpose of this study is to illustrate the analysis of premium rice price at harvest dry grain (GKP) and farmer exchange rate (NTP). The sample used is the monthly time interval from January to December in the 2019-2021 range with 36 data for each variable. Data analysis comes from secondary data taken from the Central Bureau of Statistics (BPS) report using multiple linear regression analysis test method using the SPSS application. The results showed that the price of harvested dry grains (GKP) and the price of premium rice had a positive effect on farmer exchange rates (NTP). Key words: exchange rates, farmer, rice